ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN MOTOR HONDA PADA CV NASIONAL MOTOR RUTENG - Dangga, Lende; Ngera, AprÄ±anus (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Motorcycles are a human need that really helps provide convenience in transportation. The need for motorcycles encourages people's purchasing power of motorbikes as a means of transportation. One of the alternatives used in an effort to win the competition is by selling credit concerning prices, products, credit services and credit terms. Purpose: to determine the magnitude of the influence of price, multiplied by product, credit service and credit period on sales of Honda motorcycles at CV. National Motor Ruteng. The sampling technique used the Quota sampling method, namely 100 samples who bought Honda motorbikes at CV. National Motor Ruteng. The research variables are price, product, credit service and credit term. Collecting research data using interviews, questionnaires, documentation and observation studies. Data analysis was performed using multiple regression analysis method. The results obtained (1) in terms of price, product, credit service, and credit period have a significant influence on the sales volume of Honda motorcycles at CV Nasional Motor Ruteng. (2) Simultaneously price, credit service, and credit period have a significant effect on the sales volume of Honda motorcycles at CV.Nasional Motor Ruteng (p = 0.000) where P <0.05.